Effects of Neem and Nishyinda leaves supplementation on growth performance and gut biosis in broiler (Asian Journal of Medical and Biological Research, 2020)
This study was conducted under the Department of Physiology and Pharmacology to determine the effects of Neem and Nishyinda leaves supplementation on growth performance and GUT biosis in broilers. A total of 40 day old broiler chicks were divided into four groups A, B, C and D. Group A was considered as control, fed only with commercial broiler ration. Group B supplemented with formulation of 2 gm grinded Neem leaves, Group C with 2 gm grinded Nishyinda leaves and Group D with 1 gm grinded Neem leaves plus 1 gm grinded Nishyinda leaves per liter of water respectively. Observations were recorded for live body weight, weight gain, feed consumption, feed efficiency, hemato-biochemical parameters and GUT biosis specially the parasite of birds in six weeks. Body weights were increased significantly (p0.05) differences were observed among the groups for PCV and TEC values. Hb content increased and ESR decreased significantly (p